Effects of in ovo injection of nano-selenium and nano-zinc oxide and high eggshell temperature during late incubation on antioxidant activity, thyroid and glucocorticoid hormones and some blood metabolites in broiler hatchlings - Shokraneh, Meisam; Sadeghi, Ali Asghar; Mousavi, Seyed Naser; Esmaeilkhanian, Saeid; Chamani, Mohammad (Acta Scientiarum. Animal Sciences, 2020)
This experiment was conducted to evaluate the effects of in ovo injection of nano-selenium (Nano-Se) and nano-zinc oxide (Nano-ZnO) and high eggshell temperature (EST) during late incubation on blood parameters of broiler hatchlings. A total of 750 fertile eggs, were weighed and randomly distributed among 5 treatment groups on each of 5 replicate tray levels. The injection was performed on 17 d of incubation. Treatments included of: 1) Eggs not injected and incubated at normal EST (control); 2) Eggs not injected and incubated at high EST; 3) Eggs injected NaCl solution and incubated at high EST (sham); 4) Eggs injected NaCl solution containing 40 µg Nano-Se and incubated at high EST; 5) Eggs injected NaCl solution containing 500 µg Nano-ZnO and incubated at high EST. EST of 37.8ºC (normal) or 38.9ºC (high) was applied from d 19 to 21 of incubation. In ovo injection of Nano-Se and Nano-ZnO significantly increased activity of GSH-Px and SOD and total protein, but decreased the levels of corticosterone, cortisol, T4 and T3 at high EST. Injection of Nano-Se and Nano-ZnO had a significant role in alleviating the negative effects of high temperature incubation and heat stress by increased antioxidant activity and reduced oxidative stress.